Propagation of guggal [Commiphora wightii (Arnott)] Bhand through cuttings - Singh, Jitendra; Kumawat, P.C.; Kumar, Raj; Manmohan, J.R.; Pandey, S.B.S.; Singh, Shambhu Sharan (Indian Journal of Agroforestry, 2020)
Guggal [Commiphora wightii (Arnott) Bhand] or Indian bdellium, family Burseraceae, is an important oleogum producing plant. Inadequate availability of quality planting material is a major bottleneck in commercial cultivation of guggal. Experiments were conducted separately to study the effect of time, thickness and IBA treatments on propagation of guggal by cuttings. Cuttings prepared during 30th March had early peak period of sprouting (30.62 days) and maximum rooting percentage (61.46%) was recorded. Such cuttings had maximum number (15.62) of primary roots, maximum length (32.34 cm) of longest primary roots and also the maximum length (21.81 cm) of secondary roots. Cuttings of 1.0 cm thickness took 36.05 days in peak period of sprouting, produced 55.63% rooting, showed maximum number (15.25) of primary roots, maximum length (28.99 cm) of longest primary roots and also the maximum length (17.89 cm) of secondary roots. Treatment of cuttings with 1000 ppm IBA had peak period of sprouting in 31.48 days and yielded 61.82 % rooting. The treated cuttings had maximum number (16.06) of primary roots, maximum length (30.02 cm) of longest primary roots and also the maximum length (20.08 cm) of secondary roots.